Prescription for Division ; Back Home ; Wet, Wild and Wooly [videorecording] - Lazaro, Cheche (The Probe team, 1990)
The controversy on the six medical students of the U.P. College of Medicine; Filipino overseas contract workers in the Middle East who went home due to the gulf war; Malabon Zoo, owned and managed by Manny Tangco.